Vibrio variabilis T01: A tropical marine bacterium exhibiting unique N-acyl homoserine lactone production. Issue 1 (2nd January 2016) - Mohamad, Nur Izzati; Adrian, Tan-Guan-Sheng; Tan, Wen-Si; Muhamad Yunos, Nina Yusrina; Tan, Pui-Wan; Yin, Wai-Fong; Chan, Kok-Gan
Abstract : Vibrio spp. have been widely studied for their unique properties such as pathogenicity and quorum sensing (QS) abilities. This article presents the identification of Vibrio variabilis strain T01 isolated from Malaysian coastal waters. Strain T01 of V. variabilis was identified to produce QS molecules as tested using a biosensor. High-resolution tandem mass spectrometry was used to identify N -acyl homoserine lactone (AHL) profiles of strain T01. Three AHLs, viz. N -hexanoyl-L-homoserine lactone (C6-HSL), N -(3-oxodecanoyl)-L-homoserine lactone (3-oxo-C10-HSL) and N -dodecanoyl-L-homoserine lactone (C12-HSL), were confirmed. To the authors' knowledge, this is the first documentation of AHL profiles from V. variabilis strain T01, which expands the number of QS members in Vibrio spp.